Investigation of Load and Pressure Distribution on Wing with Wake Rollup for Low Speed Aircraft - Ismail, Laith W. (Al-Khwarizmi Engineering Journal, 2018)
The presented work shows a preliminary analytic method for estimation of load and pressure distributions on low speed wings with flow separation and wake rollup phenomena’s. A higher order vortex panel method is coupled with the numerical lifting line theory by means of iterative procedure including models of separation and wake rollup. The computer programs are written in FORTRAN which are stable and efficient. The capability of the present method is investigated through a number of test cases with different types of wing sections (NACA 0012 and GA(W)-1) for different aspect ratios and angles of attack, the results include the lift and drag curves, lift and pressure distributions along the wing span taking into the consideration the effect of the angles of attack and the aspect ratios on the wake rollup. The pressure distribution on the wings shows that there is a region of constant pressure on the upper surface of the wings near the trailing edge in the middle of the wing, also there is a region of flow separation on the upper surface of the wings. A good agreement is found between the presented work results and other from previous researches. These results show that the presented method is able to capture much of flow over wings feature like separation and wake rollup.